Digitalization of Accounting: Accountant Profession in Facing Challenges of Era 5.0 - Khoirun Nisa' Syamsiyah; Driana Leniwati; Muhammad Wildan Affan (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This study aims to determine how the accounting profession responds to the issue of digitalization. This study uses a qualitative research method with a case study design. Data collection was conducted through interviews at one of the Public Accounting Firms in Malang. The findings in this study are concerned about client data leaks that affect trust in digital systems, especially in the use of Audit Tools and Linked Archive System (ATLAS) in their work, significant benefits in the efficiency and accuracy of accounting work through the use of technology, and threats to the accounting profession due to automation and the increasing risk of cybercrime. The results of this study itself offer strategic insights into dealing with changes in the landscape of the accounting profession, including strengthening data security, adapting skills, and developing policies that support digital transformation.